Funding Strategies Used by Hispanic Churches in South Florida. (Global Journal of Management and Business Research, 2025)
The congregations in the United States need help with attendance A decline in church membership results in a decrease in funds This unfavorable effect on the institution s finances can affect the congregation s operations This article seeks to assess and recommend a funding strategy for Hispanic Churches in South Florida Correspondingly Churches and other faith-based institutions require solid financial management to attain financial sustainment Congregation administrators should focus on external and internal factors financial planning and developing and maintaining collaborations with external entities to grow their finances
Keywords: personnel; personnel management; manage-ment; nonprofit; hispanic churches; faith based organizations; funding strategies; congregations